RELAY GAMES WITH NON-TRADITIONAL DIVISION OF THE HALL AS A MEANS OF DEVELOPING ORIENTATION IN SPACE AMONG ELEMENTARY SCHOOL STUDENTS - Voronova E.K. ,; Kremneva V.N. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the impact of relay games with non-traditional division of the hall on the development of orientation in space in children of primary school age. Methods and structure of the study. The pedagogical experiment was conducted with the participation of 57 second grade students of the Municipal Budgetary Educational Institution of the Petrozavodsk City District "Secondary Finno-Ugric School named after Elias Lennrot" (MBEI "Finno-Ugric School"). In the course of the experiment, an analysis was made of the results of the development of orientation in space in younger schoolchildren. At the ascertaining and control stages of the experimental work, students were offered test tasks to determine the ability to navigate on a plane (sheet of paper), the ability to navigate among objects on a plane, and graphic dictation. Results and conclusions. During the experiment, the developed methodology was implemented, consisting of six relay games with an unconventional division of the hall into the ability to navigate on a plane, the ability to navigate among objects. All relay games are designed taking into account the age characteristics of students, relay games are drawn up, the necessary equipment, the number of team members and their gender are determined. The effectiveness of the developed methodology for the development of orientation in space by means of relay races with non-traditional division of the hall is determined.